The quantitative measurement method for the radiation energy of the acoustoelectric converted wave field of building electricity. (February 2021) - Wang, Na; Wang, Chao; Zhang, Xuhong
Abstract : In order to provide the basis for the quantitative measurement of wave field radiation energy formed by building electricity and promote the development of construction industry, the quantitative measurement method for the radiation energy of the acoustoelectric converted wave field of building electricity is studied. Based on the multipole sound field of any azimuth order, the displacement potential of the sound field generated by the sound source is obtained, and the sound source model of the building electricity is established. According to the Pride theory, the acoustoelectric coupling equations are derived by using the established sound source model, and the acoustoelectric conversion of the building electricity is carried out. In this paper, the energy of Stoneley wave induced electric field in uniform medium is obtained according to the first coupling relation of acoustoelectric. The concept of electric energy density of low-frequency acoustoelectric polarization electric field is put forward, and the quantitative measurement of radiation energy of wave field is realized by deducing the specific expression. In the process of low-frequency acoustically induced polarization, the relationship between the density of electric energy and the frequency of sound wave and the permeability is obtained by simulation experiment. The results show that the energy distribution characteristics of buildings are similar when the distance between buildings is small, and the permeability and the density of electric energy are increasing.